Characterization, Classification and Evaluation of Soils of Olpad Taluka in Coastal Region of Surat District, Gujarat - Duraisamy Vasu (Journal of the Indian Society of Soil Science, 2023)
Five representative pedons (P1 Barbodhan; P2 Tena; P3 Bhandut; P4 Takrama; and P5 Karanj) from different landforms of Olpad taluka in the coastal region of Surat district, Gujarat were studied for their morphological, physical, and chemical properties. The soils were deep to very deep (100-150 cm), well to imperfectly drained, neutral to strongly alkaline (pH 7.1-9.4), non-saline to highly saline (0.2-12.6 dS m-1), low to high in organic carbon (2.2-18.7 g kg-1) and CaCO3 (5.0-18.9%), and medium to high in cation exchange capacity [35.7-70.0 cmol(p+)kg-1]. Soil texture varied from clay loam to clay with the clay content ranging from 34.2 to 55.6%. Bulk density was lower in Takrama soil (1.29-1.34 Mg m-3) than the other soils (1.30-1.55 Mg m-3). Saturated hydraulic conductivity of the soils varied from 0.1 to 1.7 cm h-1 and it was less than the critical limit of 1.0 cm h-1 in Bhandut and Karanj soils. The exchangeable sodium percentage varied from low to very high (3.6-83.6), and the pedons were generally high in exchangeable magnesium percentage (27.2-55.1). The Barbodhan pedon with the cambic horizon was classified as Typic Haplustepts, and the similar Tena pedon with vertic characteristics was classified as Vertic Haplustepts. The Bhandut, Takrama, and Karanj pedons were classified as Sodic Haplustepts, Typic Haplusterts and Sodic Haplusterts, respectively. The soils were grouped under II (Takrama), IIs (Barbodhan and Tena) and IIIws (Bhandut and Karanj) according to land capability classification.